The Association between Body Dissatisfaction, Eating Disorders, and Nutritional Status of University Students - Nugroho, Riezky Faisal; Wardani, Erika Martining (Utan Kayu Publishing, 2025)
This cross-sectional study examined whether body dissatisfaction and eating-disorder risk are associated with nutritional status among university health students in Surabaya, Indonesia. Using quota sampling, 117 students completed validated measures of body dissatisfaction (Contour Drawing Rating Scale, CDRS) and eating-disorder risk (Eating Attitudes Test-26, EAT-26); height and weight were measured to compute BMI as the indicator of nutritional status. Descriptive statistics characterized the sample, and chi-square tests assessed bivariate associations. Most respondents reported body dissatisfaction (82.1%), and 29.9% screened positive for elevated eating-disorder risk. Body dissatisfaction showed no significant association with nutritional status (p = 0.971), whereas eating-disorder risk was significantly associated with abnormal nutritional status (p = 0.003). These findings indicate a perceptual–behavioral decoupling in which dissatisfaction with body shape/size does not necessarily translate into measurable BMI differences at a single time point, while maladaptive eating behaviors are more proximally linked to weight-related outcomes. Scientifically, this contributes evidence that eating-disorder risk—not dissatisfaction per se—is the more informative correlate of nutritional status in this population. Practically, campus health programs should prioritize structured screening and early management of risky eating behaviors alongside upstream body-image literacy and counseling to reduce progression to disordered eating. Further research should test mediation/moderation pathways and employ probability sampling to strengthen generalizability. Abstrak. Penelitian potong lintang ini menelaah apakah ketidakpuasan tubuh dan risiko gangguan makan berasosiasi dengan status gizi pada mahasiswa kesehatan di Surabaya, Indonesia. Melalui teknik sampling kuota, sebanyak 117 mahasiswa mengisi instrumen tervalidasi untuk ketidakpuasan tubuh (Contour Drawing Rating Scale, CDRS) dan risiko gangguan makan (Eating Attitudes Test-26, EAT-26); tinggi dan berat badan diukur untuk menghitung Indeks Massa Tubuh (IMT) sebagai indikator status gizi. Statistik deskriptif digunakan untuk mengarakterisasi sampel, dan uji chi-kuadrat menilai asosiasi bivariat. Mayoritas responden melaporkan ketidakpuasan tubuh (82,1%), dan 29,9% tersaring memiliki risiko gangguan makan. Ketidakpuasan tubuh tidak menunjukkan asosiasi yang signifikan dengan status gizi (p = 0,971), sedangkan risiko gangguan makan berasosiasi signifikan dengan status gizi tidak normal (p = 0,003). Temuan ini mengindikasikan adanya keterputusan perseptual–perilaku, di mana ketidakpuasan terhadap bentuk/ukuran tubuh tidak serta-merta terwujud dalam perbedaan IMT pada satu titik waktu, sementara perilaku makan maladaptif lebih dekat terkait dengan luaran berbasis berat badan. Secara ilmiah, hasil ini menegaskan bahwa risiko gangguan makan—bukan ketidakpuasan tubuh semata—merupakan korelat yang lebih informatif terhadap status gizi pada populasi ini. Secara praktis, program kesehatan kampus perlu memprioritaskan skrining terstruktur dan penanganan dini perilaku makan berisiko disertai literasi citra tubuh dan konseling hulu untuk mencegah progresi menuju gangguan makan. Penelitian lanjutan sebaiknya menguji jalur mediasi/moderasi dan menggunakan sampling probabilitas untuk memperkuat generalisasi.